Strategies for Successful Anesthetic Management in Patients With Threatened Thyroid Storm: a Systematic Review of Case Reports - Fitrisyah, Aidyl; Sofiah, Nur Ilmi; Murtadh, Masagus Ahmad Rifqi; Lestari, Mayang Indah (Riviera Publishing, 2025)
Patients with uncontrolled hyperthyroidism undergoing emergency non-thyroid-related surgeries are at increased risk of perioperative complications, including thyroid storm (TS). This systematic review synthesizes findings from multiple case reports to determine optimal anesthetic management strategies. A systematic review of published case reports, including an additional case report contributed by the authors, was conducted. Cases were analyzed for anesthetic strategies, perioperative complications, and outcomes, with a focus on TS occurrence, survival rates, and risk factors. Five case reports and an additional case were reviewed. The use of beta-blockers, glucocorticoids, antithyroid drugs, and regional anesthesia was found to mitigate TS risk. General anesthesia was employed in most cases, with vigilant intraoperative monitoring. TS was reported in one case, emphasizing the need for early recognition and aggressive management. Comprehensive preoperative assessment, intraoperative vigilance, and postoperative monitoring are critical in managing patients with uncontrolled hyperthyroidism undergoing emergency surgery. Beta-blockers, steroids, and regional anesthesia appear to be key in minimizing TS risk.